Metode Sorogan Dalam Meningkatkan Pembelajaran Mufrodat Di Kelas X MIPA MA Ma’arif NU Pituruh - Faisal, Faisal; Unas, Moch Chodhiqul; Fatimah, Siti (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to determine the improvement of students' abilities in mufrodat learning through the sorogan method of class X MIPA MA Maarif NU Pituruh. This research is a classroom action research carried out for 2 cycles and each cycle consists of 2 meetings. Each cycle consists of planning, implementation, observation and reflection stages. The subject of the study was a student of class X MIPA MA Maarif NU Pituruh. The data collection technique uses tests, observations and interviews. Data validity using triangulation techniques. The results of the study showed that the sorogan method in Class X MIPA MA Maarif NU Pituruh was able to significantly improve students' ability to learn mufrodat. This can be seen from the results of pre-action, cycle I and cycle II. The results of the pre-action show that as many as 67% have not reached completeness and only 33% have reached completeness. In the first cycle, there was an increase in the percentage of completeness, which was 53%. Then